Global burden of disease among adolescents and young adults with drug use disorders, 1990–2021: based on GBD 2021 - Wang, Ming; Yu, Ting (Frontiers in Public Health, 2025)
BackgroundThe objective of this study was to assess the distribution and trends in the prevalence of drug use disorders (DUDs) among adolescents and young adults (aged 15 to 39 years), disaggregated by gender, region, country, and socio-demographic index (SDI), over the period from 1990 to 2021.MethodsUtilizing data from GBD 2021, we estimated the incidence, disability-adjusted life years (DALYs), age-standardized incidence rates (ASIR), age-standardized DALY rates, and age-standardized death rates (ASDR) for DUDs among adolescents and young adults across 204 countries and 21 regions from 1990 to 2021. Additionally, we assessed the trend of the estimated annual percentage change (EAPC).ResultsGlobally, the ASIR of new DUD cases among adolescents and young adults exhibited a decreasing trend from 1990 to 2021, with an EAPC of −0.46 (95% confidence interval: −0.52, −0.39). In 2021, the highest ASIR, age-standardized DALY rate, and ASDR were observed in high SDI areas, while the lowest rates were found in low SDI areas. The above two SDI regions demonstrated an increasing trend from 1990 to 2021. The ASIR, age-standardized DALY rates and ASDR for DUDs were consistently higher among males than females across low SDI, middle and low SDI, medium SDI, and middle and high SDI areas. The three countries with the highest ASIR were the United States (1096.05), Estonia (854.62), and New Zealand (815.92). The countries with the highest age-standardized DALY rate were the United States (3520.13), Canada (1665.49), and Estonia (1602.04). The countries with the highest ASDR were the United States (26.86), Canada (13.92), and Iceland (8.85).ConclusionThe disease burden of DUDs, measured by age-standardized DALY rates, varies across different SDI regions, with higher DALY rates observed in regions with high SDI. Additionally, gender plays a significant role in the distribution of this burden, with males experiencing a higher burden than females. Furthermore, there are distinct national and regional variations in the prevalence and trends of DUDs among adolescents and young adults.